The Influence of Employee Competence and Training through Work Motivation as an Intervening Variable on Employee Performance in Indonesian Islamic Banking - Andi Kusuma Negara; Ade Nur Alifah (FEBI IAIN Langsa, 2026)
This study aims to analyze the effect of employee competence and training on employee performance through work motivation as an intervening variable at Bank Syariah Indonesia (BSI) Area Tangerang Regency. Employee performance is an important factor in determining organizational success in achieving corporate objectives. Therefore, organizations need to continuously improve the quality of their human resources through competency development and effective training programs. This study employed a quantitative approach using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires distributed to employees of Bank Syariah Indonesia Area Tangerang Regency and analyzed using SmartPLS software. The findings indicate that employee competence has a positive and significant effect on both employee performance and work motivation. Training also has a positive and significant effect on employee performance and work motivation. Furthermore, work motivation has a positive and significant effect on employee performance. The mediation analysis reveals that work motivation successfully mediates the relationship between employee competence and employee performance, as well as the relationship between training and employee performance. These findings suggest that continuous competency development and well-designed training programs can enhance employees’ work motivation and ultimately improve their performance. Future studies are recommended to incorporate additional variables that may influence employee performance to develop a more comprehensive research model.